Identifying knowledge spillovers from universities: Quasi-experimental evidence from urban China - JING, Li (Institutional Knowledge at Singapore Management University, 2022)
This paper studies the impact of universities on local innovation activity by exploiting a unique university expansion policy in China as a quasi-experiment. We take a geographic approach, empowered by geocoded data on patents and new products at the address level, to identify knowledge spillovers as an important channel. We obtain three main findings. First, university expansion significantly increases universities’ own innovation capacity, which results in a dramatic boom of local industry patents. Second, the impact of university expansion on local innovation activities attenuates sharply within 2 kilometers of the universities. Third, university expansion boosts nearby firms’ new products and the number of times when nearby industry patents cite university patents but not the number of times when industry patents cite patents far away from universities.